KETERTARIKAN INTERPERSONAL DAN CINTA - Aliffiah Novi Ramadhini; Intan Ratna Sari, Risma Ayu Sulistyowati, Noer Aini Eldi, Sulistiasih (ADISAM PUBLISHER, 2024)
Interpersonal love refers to the emotional relationships and bonds that occur between individuals, often involving feelings of affection, intimacy, and commitment. Interpersonal love appears in many forms, including romantic love, platonic love, and familial love. The main elements commonly described in love theories include passion, emotional intimacy, and commitment decisions. This love affects a person's psychological and emotional well- being and plays an important role in social interactions and the formation of healthy and meaningful relationships.